ANALISIS PENOKOHAN DALAM CERPEN SENYUM KARYAMIN KARYA AHMAD TOHARI - Hasyim, Abdul; Anggiana, Nur Chintia; Yunus, Syarifudin (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study aims to analyze characterization in the short story "Senyum Karyamin" by Ahmad Tohari using a descriptive qualitative method and content analysis technique. The results show that Karyamin, the main character, is portrayed as patient, resilient, and optimistic despite living in poverty. Supporting characters such as Saidah, Sarji, and the village official strengthen the social and humanitarian themes, reflecting the reality of the lower-class society. The characterization is analyzed based on role, function, character development, and social representation.